Evaluation of interim MRI changes during limited-field radiation therapy for glioblastoma and implications for treatment planning. (May 2021) - Hassanzadeh, Comron; Rudra, Soumon; Ma, Sirui; Brenneman, Randall; Huang, Yi; Henke, Lauren; Abraham, Christopher; Campian, Jian; Tsien, Christina; Huang, Jiayi
Highlights: Optimal limited-field radiation therapy approaches for GBM are not well defined. Early radiological changes during RT provide insights on adequacy of limited-field. Strategies to reduced CTV margins appears not to jeopardize outcomes. Omission of T2 abnormality in selected cases is a reasonable approach. Abstract: Background and purpose: Consensus for defining gross tumor volume (GTV) and clinical target volume (CTV) for limited-field radiation therapy (LFRT) of GBM are not well established. We leveraged a department MRI simulator to image patients before and during LFRT to address these questions. Materials and methods: Supratentorial GBM patients receiving LFRT (46 Gy + boost to 60 Gy) underwent baseline MRI (MRI1) and interim MRI during RT (MRI2). GTV1 was defined as T1 enhancement + surgical cavity on MRI1 without routine inclusion of T2 abnormality (unless tumor did not enhance). The initial CTV margin was 15 mm from GTV1, and the boost CTV margin was 5–7 mm. The GTV1 characteristics were categorized into three groups: identical T1 and T2 abnormality (Group A), T1 only with larger T2 abnormality not included (Group B), and T2 abnormality when tumor lacked enhancement (Group C). GTV2 was contoured on MRI2 and compared with GTV1 plus 5–15 mm expansions. Results: Among 120 patients treated from 2014-2019, 29 patients (24%) underwent replanning based on MRI2. On MRI2, 84% of GTV2 were covered by GTV1 + 5 mm, 93% by GTV1 + 7 mm, and 98% by GTV1 + 15 mm. On MRI1, 43% of GTV1 could be categorized into Group A, 39% Group B, and 18% Group C. Group B's patterns of failure, local control, or progression-free survival were similar to Group A/C. Conclusions: Initial CTV margin of 15 mm followed by a boost CTV margin of 7 mm is a reasonable approach for LFRT of GBM. Omitting routine inclusion of T2 abnormality from GTV delineation may not jeopardize disease control.